A Soft Five-Fingered Hand Actuated by Shape Memory Alloy Wires: Design, Manufacturing, and Evaluation - Simone, Filomena; Rizzello, Gianluca; Seelecke, Stefan; Motzki, Paul (Frontiers in Robotics and AI, 2020)
This work presents a novel five-fingered soft hand prototype actuated by Shape Memory Alloy (SMA) wires. The use of thin (100 μm diameter) SMA wire actuators, in conjunction with an entirely 3D printed hand skeleton, guarantees an overall lightweight and flexible structure capable of silent motion. To enable high forces with sufficiently high actuation speed at each fingertip, bundles of welded actuated SMA wires are used. In order to increase the compliance of each finger, flexible joints from superelastic SMA wires are inserted between each phalanx. The resulting system is a versatile hand prototype having intrinsically elastic fingers, which is capable to grasp several types of objects with a considerable force. The paper starts with the description of the finger hand design, along with practical considerations for the optimal placement of the superelastic SMA in the soft joint. The maximum achievable displacement of each finger phalanx is measured together with the phalanxes dynamic responsiveness at different power stimuli. Several force measurement are also realized at each finger phalanx. The versatility of the prototype is finally demonstrated by presenting several possible hand configurations while handling objects with different sizes and shapes.